TINJAUAN TENTANG KEWAJIBAN PELAPORAN TRANSAKSI KEUANGAN OLEH ADVOKAT DALAM KETENTUAN UNDANG-UNDANG NO. 18 TAHUN 2003 TENTANG ADVOKAT YANG TIDAK SEJALAN DENGAN PERATURAN PEMERINTAH NOMOR 43 TAHUN 2015 TENTANG PIHAK PELAPOR DALAM PEMBERANTASAN DAN PENCEGAHAN TINDAK PIDANA PENCUCIAN UANG - Narada Lukman; Tatang Ruchimat (Jurnal Hukum Adigama, 2019)
The legal norms of any country are always multi-layered, where the norms below apply, are based on and come from higher norms, higher norms apply, are based and are sourced from even higher norms, up to a norm the highest is called the Basic Norm. Since the birth Republic of Indonesia with proclamation independence, as well as the adoption from the 1945 Constitution as the constitution the Indonesian State, the proof legal norm system the Republic of Indonesia, If we compare it with the theory of the level of legal norms (Stufen Theory) from Hans Kelsen and the theory of the level of legal norms, that Article 3 letter a of Government Regulation No. 43 of 2015 adheres to the Advocate Law No. 18 of 2003. Article 3 letter a Government Regulation reads "Advocates are required to report financial transactions to prevent money laundering, Advocates must report data or where the money they receive from their clients is" to ask the client about it does not feel it appropriate, because it is a secret from his client, in accordance with what is written in Article 19 which reads "Advocates have the right and obligation to keep everything confidential from their clients, including protection of files and documents against confiscation and protection against wiretapping", and Article 21 which reads "Advocates are entitled to an Honorarium for legal services that have been provided by their clients, based on the agreement of both parties".